Impact of centralized diagnostic review on quality of initial staging in Hodgkin lymphoma: experience of the German Hodgkin Study Group. (27th August 2015) - Bröckelmann, Paul J.; Goergen, Helen; Fuchs, Michael; Kriz, Jan; Semrau, Robert; Baues, Christian; Kobe, Carsten; Behringer, Karolin; Eichenauer, Dennis A.; von Tresckow, Bastian; Klimm, Beate; Halbsguth, Teresa; et al.
Summary: Accurate clinical staging is crucial for adequate risk‐adapted treatment in Hodgkin lymphoma (HL) to prevent patients from under‐ or over‐treatment. Within the latest German Hodgkin Study Group trial generation, diagnostic findings such as histopathology, computerized tomography imaging and clinical risk factors were re‐evaluated by expert panels. Here, we retrospectively analysed 5965 patients and identified 399 in who major discordant findings changed their first‐line treatment allocation. Histopathology review did not confirm the initial diagnosis of HL in 87 patients. Treatment allocation was revised in 312 of the remaining 5878 patients: 176 were assigned to a higher and 128 to a lower risk group, respectively; the correct treatment group remained unclear in 8 patients. Cases of revised treatment allocation accounted for 9·8%, 6·0%, 0·8%, and 14·8% of patients initially assigned to the HD13, HD14, HD15 trials and stage IA lymphocyte‐predominant HL project, respectively. Most revisions were due to wrong application of clinical stage (20·5% of 312 patients with revised treatment group), histological subtype (9·0%) or the risk factors ≥3 involved areas (46·8%) or large mediastinal mass (9·3%). In conclusion, centralized review by experienced experts changed risk‐adapted first‐line treatment in a relevant proportion of HL patients. Quality control measures clearly improve the accuracy of treatment and should be implemented in clinical practice.